2010
DOI: 10.1111/j.1365-2966.2010.17501.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanol line formation in outflow sources

Abstract: We report the first calculations of the spectrum of methanol, arising in shock waves in molecular outflows. The small grid of shock wave models that we have computed incorporates the results of very recent computations of the rate coefficients for the collisional excitation of methanol by ortho-and para-H 2 and by He. The two strongest transitions, one of A-and the other of E-type methanol, are masers that have been observed in a Class I methanol maser source, which is believed to be related to a molecular out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…For our LRT calculations we assumed that the A and E species of methanol are equally abundant (see e.g. Flower, Pineau Des Forêts, Rabli 2010).…”
Section: Turbulent Chemistry Model and Methanol Abundancesmentioning
confidence: 99%
“…For our LRT calculations we assumed that the A and E species of methanol are equally abundant (see e.g. Flower, Pineau Des Forêts, Rabli 2010).…”
Section: Turbulent Chemistry Model and Methanol Abundancesmentioning
confidence: 99%
“…Recent applications of MHD shock wave models to the study of outflow sources are to be found in Gusdorf et al (2008a,b), Flower, Pineau des Forêts & Rabli (2010) and Viti et al (2011). In all of these studies, the treatment of the shock wave dynamics derives from the work of Flower & Pineau des Forêts (2003), who considered the electrical charging of the grains and their influence on the dynamical and chemical profiles of the shock wave.…”
Section: Introductionmentioning
confidence: 99%
“…Given the dynamical age of the blue lobe of the L1157 outflow, which has been estimated to be only 2000–3000 yr (Gueth, Guilloteau & Bachiller 1998), the shock wave is unlikely to have reached steady state. The C‐ and CJ‐type shock wave models that we have used to simulate the spectrum of L1157 B1 incorporate a number of significant improvements on the work of Gusdorf et al (2008b) and the more recent study of methanol by Flower et al (2010). The emission‐line spectra of CO, SiO, ortho‐ and para‐H 2 O, ortho‐ and para‐NH 3 , and A‐ and E‐type CH 3 OH are all computed in a completely self‐consistent manner within the shock wave model , applying a large‐velocity‐gradient (LVG) approximation to the line transfer problem.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol has been incorporated into our MHD shock wave code, and its predictions were compared with the Herschel HIFI spectrum of L1157 B1 [5]. The equations for the escape probabilities and level populations were integrated in parallel with the dynamical and chemical rate equations.…”
Section: Shock-wave Modelmentioning
confidence: 99%